Adjuncts should always be used in pediatric regional anesthesia. Issue 1 (17th September 2014) - Lönnqvist, Per‐Arne; Morton, Neil
Summary A number of different adjuncts to local anesthetics can be used to prolong and optimize postoperative pain relief following regional anesthesia in children. The present text provides a slightly opinionated but evidence‐based argument in favor of this practice.